RESPONS MAHASISWA TERHADAP PENGGUNAAN MODUL “SEDEKAH, HIBAH, DAN HADIAH” PADA MATA KULIAH PENDIDIKAN AGAMA ISLAM DI AKADEMI FARMASI AL-FATAH BENGKULU - Nanik Nanik (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2018)
The formulation of the  problem in this  study  is how students respond to learning Islamic Education (PAI) courses using  the “Alms, Grants and  Gifts” module at the Bengkulu Al-Fatah  Pharmacy Academy. This research is in- cluded in quantitative descriptive research. The population in this study  were all third semester students at the Beng- kulu  Al-Fatah  Pharmacy Academy, while  the  research sample used  was third semester B1 students at the  Al-Fatah Pharmacy Academy  Bengkulu Academic Year 2016-2017. The instruments used  in this study were the student response questionnaire and  the module “Alms, Grants and  Gifts”. The technique of collecting data  using questionnaires and  test sheets. Based on the research that  has been done, the results show that : The average percentage score of all students is82.86764706% and is classified as very high criteria. It can be concluded that the 3rd grade B1 Semester 3-2017 Academic Year at the Al-Fatah  Pharmacy Academy gave a positive response to the learning of Islamic Education courses using the “Alms, Grants, and Gifts” module